Neighborhood Environment and Health of Injured Urban Black Men. - Palumbo, Aimee J. (J Racial Ethn Health Disparities, 2019)
INTRODUCTION: Urban black males are at disproportionately high risk of poor health outcomes, thus we need to measure neighborhood environments appropriately in order to understand aspects of neighborhoods that influence their mental and physical health. We explored associations between physical and mental health of injured, urban black men with objectively measured and perceived neighborhood characteristics. METHODS: In 2017–2018, we analyzed data from 486 black, adult males in Philadelphia admitted to a trauma center with injury between January 2013 and February 2017. Area-level measures of social, economic, and built environments were obtained from multiple sources. At enrollment, participants answered questions about neighborhood environment and self-reported physical and mental health 30 days before injury. We conducted factor analysis to identify neighborhood characteristics, then estimated odds of poor physical or mental health, accounting for spatial correlation of participants. RESULTS: Poor physical and mental health was reported by 12% and 22% of participants, respectively. In participants’ neighborhoods, 29% of adults lived in poverty. Individually, 73% of men reported abandoned buildings and 31% reported not feeling safe walking around their neighborhood. Physical health was associated with neighborhood poverty and disconnectedness. Mental health was associated with neighborhood economics and individual perceptions of social disorder and safety. Individual-level factors were not correlated with area-level factors. CONCLUSIONS: We found both area-level and individual-level measures were associated with health, perhaps operating through different mechanisms, but individual experiences may not be easily extrapolated from area-level data. By identifying important components of neighborhood environments, we may better understand how neighborhoods contribute to health in vulnerable populations.